2011
DOI: 10.1007/s12070-011-0160-7
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Hearing in Cisplatin-Induced Ototoxicity in the Guinea Pig with Intratympanic Dexamethasone

Abstract: The purpose of this study was to investigate the effectiveness of intratympanic dexamethasone injection as a therapeutic agent against cisplatin-induced ototoxicity. Animals were randomly divided into three groups. Group one received intraperitoneal cisplatin alone, group two, received intratympanic dexamethasone after cisplatin ototoxicity had been demonstrated. Group three, which is control group, received intratympanic dexamethasone.Then we made three measurements. First we measured the baseline distortion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…12 Recently, several studies have demonstrated that the intratympanic delivery of DEX minimized cisplatin-induced hearing in a frequency-related manner. [14][15][16][17] The efficiency of this strategy in treating cisplatin-induced ototoxicity was further confirmed clinically. 7 To date, the results obtained for the intratympanic delivery of glucocorticoids varied, highly depending on the dose, frequency, intensity of the cisplatin injection, and the animal models used in the experiments.…”
mentioning
confidence: 98%
“…12 Recently, several studies have demonstrated that the intratympanic delivery of DEX minimized cisplatin-induced hearing in a frequency-related manner. [14][15][16][17] The efficiency of this strategy in treating cisplatin-induced ototoxicity was further confirmed clinically. 7 To date, the results obtained for the intratympanic delivery of glucocorticoids varied, highly depending on the dose, frequency, intensity of the cisplatin injection, and the animal models used in the experiments.…”
mentioning
confidence: 98%
“…In the guinea pig, DXM diffusion across the round window membrane results in a DXM concentration gradient in the perilymph of the scala tympani (13); the lowest DXM concentrations occur farthest from the round window membrane at the apical turn and the highest concentrations are present in the basal turn where cisplatin ototoxicity is most prominent. However, IT DXM has demonstrated variable effects against cisplatin induced hearing loss in vivo (5)(6)(7)(8)(9)(10)(11). One randomized clinical trial of 15 patients demonstrated that IT DXM can reduce hearing threshold shifts at 6000 Hz and lower OHC dysfunction as determined by the distortion product otoacoustic emissions (4000-8000 Hz); the results were significant despite a small sample size (12).…”
Section: Discussionmentioning
confidence: 99%
“…No significant protection of OHC viability of the basal turn was observed at a lower dose of DXM (i.e., 75 mg/mL) in explants exposed to 2, 5, and 10 mM of cisplatin in vitro. These findings suggest that the variability in IT DXM protection against cisplatin ototoxicity demonstrated in animal and human studies may be a result of insufficient levels of DXM accumulating in the perilymph fluid within the scala tympani of the inner ear (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations